2005
DOI: 10.1007/s00535-004-1492-9
|View full text |Cite
|
Sign up to set email alerts
|

MyD88-deficient mice develop severe intestinal inflammation in dextran sodium sulfate colitis

Abstract: These findings suggest that, via MyD88 signaling, the innate immune system in the gut plays an important protective role in colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
170
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(179 citation statements)
references
References 44 publications
8
170
1
Order By: Relevance
“…MyD88 deficiency was shown to prevent colitis in Il-10 -/-as well as NEMO IEC-KO mice [23,31], demonstrating that MyD88 signaling exerts detrimental colitogenic effects in these models. In contrast, Myd88 -/-mice are hypersensitive to DSS-induced colitis [42,43], indicating that MyD88 also serves an essential protective role in the intestine. Being an essential adaptor protein for TLR-induced NF-κB activation, it seems likely that the opposing effects of bacteria-induced MyD88 signaling reflect the colitogenic and protective functions of NF-κB activity in the intestine.…”
Section: Mechanisms Underlying the Dual Role Of Intestinal Nf-κb Actimentioning
confidence: 99%
“…MyD88 deficiency was shown to prevent colitis in Il-10 -/-as well as NEMO IEC-KO mice [23,31], demonstrating that MyD88 signaling exerts detrimental colitogenic effects in these models. In contrast, Myd88 -/-mice are hypersensitive to DSS-induced colitis [42,43], indicating that MyD88 also serves an essential protective role in the intestine. Being an essential adaptor protein for TLR-induced NF-κB activation, it seems likely that the opposing effects of bacteria-induced MyD88 signaling reflect the colitogenic and protective functions of NF-κB activity in the intestine.…”
Section: Mechanisms Underlying the Dual Role Of Intestinal Nf-κb Actimentioning
confidence: 99%
“…Commensal bacteria contribute to tissue protection and repair by stimulating TLRs, which are best known for their essential functions in pathogen detection and protection from infection (8). Mice deficient in TLR2 and TLR4 (which recognize conserved bacterial products such as lipopeptides and LPS) or the TLR signaling adaptor myeloid differentiation factor 88 (MyD88) are phenotypically similar to germfree mice with regard to protection from intestinal injury and subsequent compensatory proliferation (5,7,9,10). Thus perception of injury and induction of tissue repair processes may occur via recognition of commensal microbial products that gain access to the TLRs expressed on myeloid cells upon epithelial barrier disruption (7,11).…”
Section: Innate Immune Recognition Of the Commensal Microflora As A Cmentioning
confidence: 99%
“…We and others have used an acute model of colitis to address the function of TLR4 in the setting of epithelial injury and inflammation. Administration of DSS to animals genetically deficient in TLR4 or MyD88 results in greater toxicity manifested by increased rectal bleeding, weight loss and mortality compared to wild-type littermates [14][15][16] . We have also found that animals deficient in TLR4 or MyD88 have decreased neutrophil recruitment to the intestine due to defective expression of chemokines and they experience bacterial translocation to mesenteric lymph nodes 15 .…”
Section: Introductionmentioning
confidence: 99%